Major Constituents From Brucea javanica and Their Pharmacological Actions - Zhang, Juan; Xu, Hong-Xi; Dou, Yao-Xing; Huang, Qiong-Hui; Xian, Yan-Fang; Lin, Zhi-Xiu (Frontiers in Pharmacology, 2022)
Brucea javanica (Ya-dan-zi in Chinese) is a well-known Chinese herbal medicine, which is traditionally used in Chinese medicine for the treatment of intestinal inflammation, diarrhea, malaria, and cancer. The formulation of the oil (Brucea javanica oil) has been widely used to treat various types of cancer. It has also been found that B. javanica is rich in chemical constituents, including quassinoids, triterpenes, alkaloids, and flavonoids, which exhibit various biological properties. Pharmacological studies have revealed that chemical compounds derived from B. javanica exhibit multiple bioactivities, such as anti-cancer, anti-bacterial, anti-diabetic, and others. This review provides a comprehensive summary on the pharmacological properties of the main chemical constituents presented in B. javanica and their underlying molecular mechanisms. Moreover, the review will also provide scientific references for further research and development of B. javanica and the chemical constituents into novel pharmaceutical products for disease management.